The textual influences of Jacob Ledesma’s catechism and the catechism of Mikalojus Daukša on the anonymous catechism of 1605 - Smetonienė, Anželika (Kalbotyra, 2017)
The article compares the relationship between the texts of the Polish Ledesma’s catechism, the catechism of Mikalojus Daukša and the catechism of 1605. The problem of the source for the Polish translation of Ledesma’s text and, consequently, for the two Lithuanian versions of the catechism is briefly introduced: scholarly opinions differ as to when the Italian original of Ledesma’s catechism was published. Likewise unknown is the exact date of the translation of Ledesma’s catechism into the Polish language. Both Lithuanian translations were accomplished from the Polish Ledesma’s catechism; however, there are significant differences between them. Daukša was the first to accomplish a translation of such nature into Lithuanian, whereas the anonymous translator of the catechism of 1605 used not only the Polish source, but also Daukša’s catechism, which had been rendered ten years earlier. Although the relationship between the latter text and the Polish translation as well as the Italian original has already been investigated, the comparison of the catechism of 1605 to the Polish version of Ledesma’s catechism and to the catechism translated by Daukša still needs to be drawn. The aim of the present article is to compare the three catechisms and to investigate the textual influence of Daukša’s catechism (which had been published earlier) on the anonymous translation of the catechism of 1605; in other words, to determine whether the catechism of 1605 was translated directly from the Polish catechism of Ledesma, or whether the translator relied more on the text of Daukša’s catechism; also, to identify the authorial lines of the anonymous author.
Keywords: Daukša; anonymous catechism; Ledesma; translation; Polish; Italian original